Developing interethnic tolerance of students in foreign language lessons - Yakubbayev Murodilla Marufovich (THOT Publishing House, 2021)
The article discusses the problem of forming interethnic tolerance in students. The sequence of development of the model of formation of interethnic tolerance in students of nonphilological education of higher educational institution is shown. The stages of formation of interethnic tolerance, the goals and objectives of the formation of this personal quality at each stage, as well as the methods of formation of interethnic tolerance in students through the design model are highlighted.